Performance Study of a New Phase Transition Flat Heat Pipe Radiator - WANG Xiaoyuan; WANG Xiong; LI Yanyong; YANG Jinfeng (Kongzhi Yu Xinxi Jishu)
Based on an industrial module, it designed a phase transition flat heat pipe radiator and analyzed its structure and technical feature. Simulation analysis of multi-operating conditions was carried out with software and performance change rule of the radiator was obtained. In the meantime, comparison between the phase transition flat heat pipe radiator and the gravity heat pipe radiator was made based on the test. Results show that thermal resistance of the phase transition flat heat pipe radiator is reduced significantly and its temperature is uniformly distributed, which can improve the electrical performance of power module.